The Genetic Algorithm for Interoperability Cost Optimization: A Case Study of GIMAC Business Network (African Journal for Industrial and Applied Mathematics, 2025)
Interoperability cost analysis is a continuous trend in enterprise information systems. Researchers have made the most significant contributions in thisfield. The problem we address is to show how to optimize interoperability costswithin a networked enterprise. To overcome this issue, we have used a geneticalgorithm in which, the fitness function that we have defined is a new model foroptimizing the interoperability cost. To show how organizations validate and verify the solutions obtained through interoperability cost analysis and what measuresare taken to ensure the accuracy and reliability of the results, we have conducteda case study within a networked enterprise. The results of the interoperability costanalysis show that the inter-organizational business process studied is not adaptedto the interoperable information system and does not allow the evolution of thenetwork after a certain number of years.